GEN Z’S CONTINUANCE USAGE INTENTION OF GOPAY MEDIATED BY ATTITUDE - Gunawan, Lenny; Samuel, Zeann (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The use of e-wallet services in the digital society has become a common transaction activity. Thus, multiple companies developed e-wallets to fulfill the industry's user needs. Generation Z, youngsters aged 12 to 27, are tech savvy. With the existence of e-wallets, Generation Z is used to the fast ecosystem. Thus, Generation Z tends to use e-wallets more than the previous generations. This fact is supported by multiple surveys stating that Generation Z uses e-wallets more frequently than the other generation. From this research, perceived ease of use and perceived usefulness as the independent variable have significant effects on the continuance intention of Generation Z in Surabaya. Attitude as the mediation variable also has a significant effect on the perceived usefulness and perceived ease of use towards continuance intention. Thus, Gopay e-wallet developer must ensure their understanding of the factor that makes the users use the application easily, efficiently, time efficiently, cost efficiently, and effortlessly to obtain users’ likability and positive attitude towards the application.